Airway support using a pediatric intubation tube in adult patients with atrial fibrillation: A simple and unique method to prevent heart movement during catheter ablation under continuous deep sedation. Issue 4 (21st February 2017) - Takigawa, Masateru; Takahashi, Atsushi; Kuwahara, Taishi; Okubo, Kenji; Nakashima, Emiko; Watari, Yuji; Yamao, Kazuya; Nakajima, Jun; Tanaka, Yasuaki; Takagi, Katsumasa; Kimura, Shigeki; Hikita, Hiroyuki; et al.
Abstract: Background: The present study aimed to elucidate the safety and effectiveness of a noble and unique airway management technique in which a pediatric intubation tube is used in adult patients with atrial fibrillation (AF) undergoing catheter ablation (CA) under continuous deep sedation. Methods: In total, 246 consecutive patients with AF (mean age, 65±10 years; 60 women) underwent CA under dexmedetomidine‐based continuous deep sedation. A 4‐mm pediatric intubation tube guided by a 10‐French intratracheal suction tube was inserted smoothly, and the tip of the tube was located at the base of the epiglottis. The maximum shifting distance of the heart (MSDH) was measured with the 3D mapping system (Ensite NavX system) before and after inserting the pediatric intubation tube. Results: At baseline, the MSDH of patients under continuous deep sedation was 23±14 mm. The pediatric intubation tube reduced the MSDH to 13±6 mm (mean reduction from baseline, 38.4±21.7%; P <0.0001). In contrast, oxygen saturation was significantly increased from 89±8% to 95±3% ( P <0.0001). The mean distance between the nostril and base of the epiglottis was 16.6±0.5 mm. Major periprocedural complications occurred in 9 (3.6%) patients including 3 (1.2%) cardiac tamponade and 6 (2.4%) phrenic nerve injury cases. Larger MSDH (odds ratio, 1.13; 95% confidence interval, 1.04–1.25; P =0.007) was a significant predictor of major periprocedural complications. No major airway complications occurred, except in 3 patients (1.2%) who had minor nasal bleeding. Conclusion: This unique airway management technique using a pediatric intubation tube for CA procedures performed in adult patients with AF under continuous deep sedation was easy, safe, and effective.